2013
DOI: 10.1128/aac.00238-13
|View full text |Cite
|
Sign up to set email alerts
|

Relative Fecal Abundance of Extended-Spectrum-β-Lactamase-Producing Escherichia coli Strains and Their Occurrence in Urinary Tract Infections in Women

Abstract: Extended-spectrum-beta-lactamase (ESBL)-producing Escherichia coli (ESBL E. coli) strains are of major concern because few antibiotics remain active against these bacteria. We investigated the association between the fecal relative abundance (RA) of ESBL-producing E. coli (ESBL-RA) and the occurrence of ESBL E. coli urinary tract infections (UTIs). The first stool samples passed after suspicion of UTI from 310 women with subsequently confirmed E. coli UTIs were sampled and tested for ESBL-RA by culture on sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
3
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 30 publications
2
73
3
3
Order By: Relevance
“…Of note, ESBL-RA in patients without antibiotic exposure was similar to that observed in European women [1.1%] [8]. ESBL-RA was not found to be associated with age, pregnancy, antibiotics use …”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Of note, ESBL-RA in patients without antibiotic exposure was similar to that observed in European women [1.1%] [8]. ESBL-RA was not found to be associated with age, pregnancy, antibiotics use …”
Section: Resultsmentioning
confidence: 55%
“…CFUs were counted in decimal logarithms at the dilution in which 1-100 CFUs grew. ESBLrelative abundance (ESBL-RA) was calculated as the ratio of the ESBL-E. coli counts divided by the total number of Enterobacteriaceae [8]. For women who carried more than one ESBL E. coli, only the ESBL-RA of the dominant clone was considered.…”
Section: Microbiological Analysismentioning
confidence: 99%
“…In recent years, extended-spectrum β-lactamases (ESBLs) have increased in type and frequency, such as enterobacteriaceae and carbapenemases, which have resulted in a worldwide dissemination of such extended spectrum β-lactamases producing strains [21]; production of extended spectrum β-lactamases (ESBLs) is currently a matter of increasing global concern [5,22]. Ruppe and Cols identified that the occurrence of UTI caused by ESBL E. coli in women who were not exposed to antibiotics was linked to the relative amount of fecal ESBL E. coli [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that a high relative abundance (RA) of ESBL E. coli in the feces increases the risk of urinary tract infection (UTI) by ESBL E. coli (3). Additionally, a high ESBL E. coli RA has been associated with longer fecal carriage time, increasing the numbers of excreted E. coli in the environment and the potential risk of dissemination of these resistant strains (4).…”
mentioning
confidence: 99%
“…Although controversial, several works have suggested that the RA of various E. coli clones present in the feces plays a key role in the pathogenesis of UTIs, probably because the dominant E. coli clone would have the maximum likelihood to colonize the urinary tract (14). Subsequently, a high RA of ESBL E. coli in the feces increases the risk of UTI by ESBL E. coli (3). Similarly, during bacterial translocation from the gut leading to bacteremia, the translocating bacteria, including E. coli, have been found to be mostly the dominant gut colonizer (15).…”
mentioning
confidence: 99%